Epistasis between neurochemical gene polymorphisms and risk for ADHD - GILL, MICHAEL; HAWI, ZIARIH (My University, 2011)
A number of genes with function related to synaptic neurochemistry have been genetically associated with attention deficit/hyperactivity disorder. However, susceptibility to the development of common psychiatric disorders by single variants acting alone, can so far only explain a small proportion of the heritability of the phenotype. It has been postulated that the unexplained 'dark heritability' may at least in part be due to epistatic effects, which may account for the small observed marginal associations, and the difficulties with replication of positive findings. We undertook a comprehensive exploration of pair-wise interactions between genetic variants in 24 candidate genic regions involved in monoaminergic catabolism, anabolism, release, re-uptake and signal transmission in a sample of 177 parent-affected child trios using a case-only design and a case-pseudocontrol design using conditional logistic regression. Marker-pairs thresholded on interaction odds ratio (OR) and P-value are presented. We detected a number of interaction ORs >4.0, including an interesting correlation between markers in the ADRA1B and DBH genes in affected individuals, and several further interesting but smaller effects. These effects are no larger than you would expect by chance under the assumption of independence of all pair-wise relations; however, independence is unlikely. Furthermore, the size of these effects is of interest and attempts to replicate these results in other samples are anticipated
PUBLISHED
PMID: 21368917
Keywords: Psychiatry; Genes & Society